2017
DOI: 10.1080/20008198.2019.1583524
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of correlates of prolonged grief disorder in adults exposed to violent loss

Abstract: Background: Violent loss (i.e. loss through homicide, suicide, or accident) is associated with high levels of prolonged grief disorder (PGD). Objective: The current meta-analysis aims at identifying correlates of PGD in adults exposed to violent loss. Method: We conducted a systematic literature search in PsycINFO, PsycARTICLES, PubMed, Web of Science, and Scopus. We used the Pearson correlation coefficient r as an effect size measure and a random effects model was applied to calculate effect sizes. Results: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
112
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(142 citation statements)
references
References 91 publications
23
112
2
5
Order By: Relevance
“…What we do not know is how the neurobiological (Lanius & Olff, 2017), psychological (Baekkelund, Frewen, Lanius, Ottesen Berg, & Arnevik, 2018;Schafer, Becker, King, Horsch, & Michael, 2019), affective (Strøm, Aakvaag, Birkeland, Felix, & Thoresen, 2018), and relational (Heeke, Kampisiou, Niemeyer, & Knaevelsrud, 2019;van Dijke, Hopman, & Ford, 2018) alterations associated with different forms, durations, and structures (Armour, Fried, & Olff, 2017;Murphy, Elklit, Dokkedahl, & Shevlin, 2018) of psychotrauma exposure (and reexposure) emerge and take different courses or trajectories across the lifespanand across generations (Burnette & Cannon, 2014;Crombach & Bambonye, 2015;Schick, Morina, Klaghofer, Schnyder, & Muller, 2013). Biopsychosocial mechanisms and processes involved in the long-term adverse impact of childhood trauma over decades into mid-life and old age (Glück, Knefel, Tran, & Lueger-Schuster, 2016) and across generations (Kuffer, Thoma, & Maercker, 2016) have been preliminarily conceptualized but remain understudied.…”
Section: Trauma Exposure and Impact Across The Lifespanmentioning
confidence: 99%
“…What we do not know is how the neurobiological (Lanius & Olff, 2017), psychological (Baekkelund, Frewen, Lanius, Ottesen Berg, & Arnevik, 2018;Schafer, Becker, King, Horsch, & Michael, 2019), affective (Strøm, Aakvaag, Birkeland, Felix, & Thoresen, 2018), and relational (Heeke, Kampisiou, Niemeyer, & Knaevelsrud, 2019;van Dijke, Hopman, & Ford, 2018) alterations associated with different forms, durations, and structures (Armour, Fried, & Olff, 2017;Murphy, Elklit, Dokkedahl, & Shevlin, 2018) of psychotrauma exposure (and reexposure) emerge and take different courses or trajectories across the lifespanand across generations (Burnette & Cannon, 2014;Crombach & Bambonye, 2015;Schick, Morina, Klaghofer, Schnyder, & Muller, 2013). Biopsychosocial mechanisms and processes involved in the long-term adverse impact of childhood trauma over decades into mid-life and old age (Glück, Knefel, Tran, & Lueger-Schuster, 2016) and across generations (Kuffer, Thoma, & Maercker, 2016) have been preliminarily conceptualized but remain understudied.…”
Section: Trauma Exposure and Impact Across The Lifespanmentioning
confidence: 99%
“…Norway, where this study took place, has one of the highest reported prevalence rates of overdose in Europe (Norwegian Directorate of Health 2019, p. 5). As other research on bereaved persons following sudden and unexpected, self-inflicted or violent deaths has demonstrated that unnatural deaths are related to an increased prevalence of complicated grief among this population (Dyregrov et al 2003;Heeke et al 2017), there is need for particular attention to the situation of bereaved left behind after DRDs. Prolonged grief disorder (PGD) is by far the most common form of complicated grief.…”
Section: Introductionmentioning
confidence: 99%
“…A minority of approximately 10% of bereaved individuals is plagued by persistent and disabling distress [1,2]. This distress may manifest in symptoms of prolonged grief disorder (PGD; 3) or persistent complex bereavement disorder (PCBD) as included in DSM-5 [4]-including yearning, difficulties in accepting the loss, and moving on without the lost personas well as depression, posttraumatic stress disorder (PTSD), other anxiety disorders, and suicidal ideation that are frequently comorbid with PGD/PCBD [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…There is gradually growing knowledge about risk factors for poor bereavement outcome. Research has shown that disturbed grief is associated with loss of closer loved ones, losses due to unnatural/violent causes, limited social support, and personality features of insecure attachment and elevated neuroticism [5,7]. Yet, there is a need to enhance knowledge about risk factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation